1983
DOI: 10.1002/bjs.1800701008
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of postoperative renal failure in patients with obstructive jaundice—the role of bile salts

Abstract: Preoperative administration of the simple bile salt sodium deoxycholate has been shown in this study to prevent postoperative endotoxaemia and renal failure in patients with obstructive jaundice. Fifty-four per cent of jaundiced patients not given the salt were found to have systemic endotoxaemia, associated with renal impairment in two-thirds of the cases. No patient given sodium deoxycholate 500 mg 8 hourly for 48 hours before operation had portal or systemic endotoxaemia, and none had evidence of renal impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
2
3

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(52 citation statements)
references
References 25 publications
3
44
2
3
Order By: Relevance
“…In the present study, expression of markers of ER stress were generally lower in mice treated with bile acids; however, fructose feeding seemed not to have been associated with an enhancement of ER stress in the duodenum of mice compared to water controls. It also has been suggested by the results of other groups that bile acids may inhibit bacterial growth in the intestine ( 26,48,49 ). However, in the present study, the protective effects found in fructose-fed mice concomitantly treated with bile acids were not associated with changes in number of bacteria in the duodenum.…”
Section: Discussioncontrasting
confidence: 68%
“…In the present study, expression of markers of ER stress were generally lower in mice treated with bile acids; however, fructose feeding seemed not to have been associated with an enhancement of ER stress in the duodenum of mice compared to water controls. It also has been suggested by the results of other groups that bile acids may inhibit bacterial growth in the intestine ( 26,48,49 ). However, in the present study, the protective effects found in fructose-fed mice concomitantly treated with bile acids were not associated with changes in number of bacteria in the duodenum.…”
Section: Discussioncontrasting
confidence: 68%
“…First, three studies used external biliary drainage only, 26,32,35 six studies reported on the use of only internal biliary drainage, 27,30,33,34,37,40 and most studies used both. 11,14 -16,22-25,28,29,31,36,38,39 Although both decompress the biliary tract, the pathophysiologic consequence of internal drainage is entirely different from that of external drainage in terms of restoration of the enterohepatic cycle, 43,44 colonization of the biliary tract, 12,45 and inflammatory reaction of the biliary tract. 13 Second, different levels of biliary obstruction are compared as one.…”
Section: Discussionmentioning
confidence: 99%
“…Among these adverse effects are suppression of cellular immunity [26], hemodynamic disturbances [27], induction of intravascular coagulation [28], and metabolic derangements [29]. There is plenty of clinical and experimental evidence showing the presence of systemic endotoxemia in obstructive jaundice and endotoxin, and through its direct or indirect harmful effects, it has been implicated in the pathophysiology of obstructive jaundice [30, 31]. In addition to bacterial overgrowth promoted by the absence of intraluminal bile, altered intestinal barrier function is also thought to be responsible for the increased translocation of bacteria and their toxins from the lumen to normally sterile extraintestinal sites including liver, mesenteric lymph node complex, spleen, and blood [32].…”
Section: Discussionmentioning
confidence: 99%